2014
DOI: 10.4183/aeb.2014.396
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Dose, Open-Label, Prospective Clinical Study of Denosumab in Patients with Primary Hyperparathyroidism

Abstract: Background. The purpose of this study was to observe the effects of denosumab on bone mineral density (BMD), bone turnover markers and serum calcium in patients with primary hyperparathyroidism (PHPT) and osteoporosis.Methods. Seven consecutive patients with PHPT were administered a single subcutaneous injection of denosumab, 60 mg. The subjects were followed up to 6 months: serum calcium on days 1,3,7,14,30 and at 3 months and 6 months; serum intact parathyroid hormone (iPTH), C-telopeptide (CTX) and N-mid os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…There were five studies in which denosumab was given to PHPT patients, of which two were excluded because data were not presented in the required format ( 31 , 32 ). The remaining three studies were included in the meta-analysis ( 21 , 25 , 26 ). There were two studies in which the effect of BPs was compared with PTX ( 15 , 20 ) and one study in which combination of BP and PTX was compared with PTX ( 22 ) in PHPT patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were five studies in which denosumab was given to PHPT patients, of which two were excluded because data were not presented in the required format ( 31 , 32 ). The remaining three studies were included in the meta-analysis ( 21 , 25 , 26 ). There were two studies in which the effect of BPs was compared with PTX ( 15 , 20 ) and one study in which combination of BP and PTX was compared with PTX ( 22 ) in PHPT patients.…”
Section: Resultsmentioning
confidence: 99%
“…There was no effect on serum phosphate with ALN use. Only two denosumab studies measured serum calcium; in one, a decline in serum calcium was observed during the first month, after which it returned to baseline levels and continued until 50 weeks ( 21 ); and in the second, a decrease in serum calcium was observed in the first two weeks but then returned to the baseline levels and continued throughout the study (6 months) ( 26 ). PHPT is characterized by cortical bone loss with relative preservation of trabecular bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Информация о влиянии деносумаба** на прирост МПК у пациентов с ПГПТ ограничена [283][284][285][286]. Однако по результатам рандомизированного плацебо-контроируемого двойного слепого исследования 3-ей фазы DENOCINA использование деносумаба** в дозе 60 мг 1 раз в 6 мес.…”
Section: уровень убедительности рекомендаций в (уровень достоверности...unclassified
“…Serum calcium varied between 10.65 and 12.4 mg/dL, PTH from 167 pg/mL to 567 pg/mL for four years. In the fifth year calcium rose to 13.5 mg/ dL and PTH to 1200 pg/mL and became refractory to iv bisphosphonates; denosumab was added as described (11,12). No OF or renal lesions were identified.…”
Section: Case Presentationmentioning
confidence: 99%